The tax system penalizes the growth of new and small businesses in the EU - Barrios Salvador; Delis Fotis; Landabaso Mikel (European Commission, Joint Research Centre (JRC), 2024)
We provide evidence on the differences in the effective tax rate by firm size, highlighting that effective tax rates tend to follow a bump-shaped curve, increasing from micro to small firms and then decreasing for medium to large firms. Our analysis, based on microdata from several EU countries, shows that both corporate and labour taxation follow this pattern. Econometric analysis reveals that a 1% increase in effective corporate taxation results in a 2.6% decrease in firm turnover growth, with new firms and micro firms being particularly affected. The negative impact of corporate taxation on firm growth is much larger for new firms compared to older firms, and this is especially pronounced in Spain, where a 1% tax hike leads to a turnover growth decrease of 8%. Examining the 2015 Spanish corporate tax reduction for new firms, we find that the reform's overall positive impact was insignificant for micro firms, suggesting the need for more targeted policies considering firm size, age, and ownership.
Keywords: 330